Are repeatedly victimized households different? - Osborn, Denise R. (Journal of quantitative criminology, 1996)
Much recent victimization research has concentrated on predicting who will be victimized, with relatively little concern for the number of events suffered. This study turns to the latter issue by focusing attention on the prediction of repeat victimization. A statistical methodology is employed which allows for the explicit recognition that an initial victimization must occur prior to any repeat event. When applied to property crime information from the 1984 British Crime Survey, we find little evidence that repeat victims have distinctive characteristics compared with single victims. Nevertheless, households with characteristics which protect from victimization, in the sense of giving rise to a low initial risk, have this protection reduced for a subsequent event. Moreover, comparing two households with different risk characteristics, their repeat victimization probabilities are more similar than were those for the initial occurrence.